PREVALENCE AND MOLECULAR DIAGNOSIS OF THEILERIA ANNULATA IN BOVINE FROM THREE DISTINCTS ZONES OF KHYBER PAKHTUNKHWA PROVINCE, PAKISTAN - S. H. Farooqi1; M. Ijaz; M. H. Saleem; M. I. Rashid; S. S. Ahmad; S. Islam; A. I. Aqib; A. Khan; K. Hussain; N. U Khan1. (Journal of Animal and Plant Sciences, 2017)
Tropical theileriosis is a tick-borne hemoparasitic disease and is responsible for huge economic losses in livestock sector of Pakistan. Bovine of three distinct zones of Khyber Pakhtunkhwa (KPK) province were examined to determine the molecular prevalence of T. annulata along with associated risk factors. A total of 900 blood samples (n=479 cows; n=421 buffaloes) were collected and examined; 170 (18.88%) were found positive for T. annulata. The central zone showed greater prevalence 65/300 (21.67%), followed by southern zone 56/300 (18.67%) and northern zone 49/300 (16.33%). A significant difference (P< 0.05) was observed in cows as compared to buffalo population (P > 0.05). Univariate analysis of risk factors including temporal zones, species, breeds, sexes, age, management systems, tick infestation, previous tick history, tick control, types of acaricides used and interval of acaricides usages revealed a significant (P< 0.05) association with prevalence of T. annulata in bovine. This study will help in developing more effective control of T. annulata in bovine of Pakistan. The results revealed here will help in developing more effective control strategies in future for dairy farmers in Pakistan.
Keywords: Theileria annulata; Prevalence; Risk factors; Temporal Zones